Solid-liquid filtration : a user's guide to minimizing cost and environmental impact; maximizing quality and productivity - 524922 Sparks, Trevor ([Oxford] ; Waltham, M.A. : Butterworth-Heinemann, 2012)
Includes bibliographical references (p. 181) and index.